Socio-Legal Studies and the Implementation of Law No. 1 of 2023 - Tirtakusuma, Andreas Eno (Yayasan Baru Haji Samsudin, 2026)
This study explores the role of the socio-legal approach in law enforcement, emphasizing the interaction between legal texts and social realities. Using a qualitative methodology, specifically literature review and library research, the article investigates key legal theory concepts, including Lawrence M. Friedman's framework of the legal system consisting of structure, substance, and legal culture, as well as Soerjono Soekanto’s identification of five crucial factors influencing law enforcement. The study also incorporates Richard A. Posner’s economic analysis of law, particularly in criminal law, and highlights the significance of legal culture in shaping public legal awareness. The findings indicate that law enforcement should not be viewed solely through a normative lens but must integrate social, cultural, and economic dimensions to understand its full impact. In the context of the enactment of Law No. 1 of 2023 (the new Indonesian Penal Code), the application of this law requires a thorough understanding of the socio-legal approach, which can help judges make more informed and contextually just decisions. The socio-legal approach provides a comprehensive perspective, bridging the gap between written law and its practical application, and offers recommendations for creating legal policies that are more attuned to societal needs. This research contributes to advancing the understanding of the importance of integrating legal theory with social sciences to foster a more just and effective legal system.